ATRX and the replication of structured DNA. - Clynes, D; Gibbons, R (Elsevier, 2013)
Understanding the underlying molecular basis for disease can often be a prolonged and tortuous process with many false leads and blind alleys. Relating the cause of ATR-X syndrome to the function of the protein ATRX is a case in point. In this review we attempt to bring together the diverse biological phenomena associated with ATRX dysfunction with what has recently been discovered concerning the chromatin remodelling activity of this protein. This potentially casts light on how defective DNA replication/histone replacement can impact on transcription, telomere maintenance and also possibly chromosome segregation.